Beastly - Flinn, Alex (Flinn, Alex. Kendra chronicles, 2007)
A modern retelling of "Beauty and the Beast" from the point of view of the Beast, a vain Manhattan private school student who is turned into a monster and must find true love before he can return to his human form.